The helminth endoparasite type specimens of the Museum Zoologicum Bogoriense, Indonesia - Animalesto, Gloria; Dewi, Kartika; Apriyanti, Yuni (Zootaxa, 2022)
A list of the type specimens of helminth endoparasites in the Museum Zoologicum Bogoriense (MZB), Indonesia, is presented. There are types of 93 helminth endoparasite species consisting of 63 species of nematodes, 22 species of cestodes, and 8 species of trematodes that have been deposited in MZB. Altogether, there are currently 211 deposited numbers of type-specimens at MZB, which contain 817 specimens wet preserved and 85 specimens mounted. The list has now been added to the scientific publication record and museum catalog.